"People look at me like I AM the virus": Fear, stigma, and discrimination during the COVID-19 pandemic. (March 2021) - Choi, Shinwoo
Anti-Asian sentiment is surging because of COVID-19 and there have been incidents of hate crime. This paper presents a reflection by an Asian social work researcher on the impact of this surge on herself and other Asians in America. Reflecting on the history of pandemic, racism against Asian Americans, and anti-Chinese sentiment among other Asian group, the paper provides important points for us to ponder as a community of social workers in the topics of racial justice